Association of iodine‐related knowledge, attitudes and behaviours with urinary iodine excretion in pregnant women with mild iodine deficiency. Issue 2 (18th November 2020) - Wang, Z.; Wu, Y.; Shi, Z.; Song, J.; Wang, G.; Xu, C.; Song, Q.; Jin, W.; Cui, X.; Wu, C.; Zang, J.; Guo, C.
Abstract: Background: Subsequent to the implementation of the universal salt iodisation policy, China has all but eliminated the iodine deficiency disorders. However, pregnant women are still experiencing mild iodine deficiency. The present study explored factors that could relate to mild iodine deficiency in pregnant women. Methods: In total, 2400 pregnant women were enrolled using a multistage, stratified, random sampling method in Shanghai. Data were collected via a standardised questionnaire. The urine samples and household cooking salt samples were collected for the detection of urinary iodine and salt iodine concentrations. Results: The median urinary iodine concentration (MUIC) was 148.0 μg L −1 for all participants, and 155.0 μg L −1, 151.0 μg L −1 and 139.6 μg L −1 in the first, second and third trimesters. The MUIC in the third trimester was significantly lower than that of the first trimester ( P < 0.05). The usage rates of iodised salt and qualified‐iodised salt were 71.5% and 59.4%, respectively. Iodine‐related knowledge score composition ratio was significantly different between the high and low UIC groups ( P < 0.05). Participants' MUIC increased significantly with the increases in iodine‐related knowledge score ( P < 0.001). The third trimester was a significant risk factor for high UIC, whereas high iodine‐related knowledge score, actively learning dietary knowledge and having a habit of consuming iodine‐rich food were significant protective factors for high UIC ( P < 0.05). Conclusions: Iodine level is adequate among pregnant women in Shanghai during the first and the second trimesters, although it is is insufficient in the third trimester. Good iodine‐related knowledge, attitudes and behaviours are important for pregnant women with respect to maintaining adequate urinary iodine. Abstract : Iodine level is adequate among pregnant women in Shanghai during the first and the second trimesters, although it is insufficient in the third trimester. Good iodine‐related knowledge, attitudes and behaviours are important for pregnant women to maintain adequate urinary iodine.